2020
DOI: 10.21303/2613-5647.2020.001306
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Development of Entrepreneurial Competencies

Abstract: Entrepreneurship can be perceived as an individual's ability to identify opportunities, and to develop solutions that create innovative solutions for society. It can be a business, a project or even a movement that generates real change and impact on people's daily lives. What defines an entrepreneur is his/her behavior and attitudes and not personality traits or any other innate characteristics. It is not possible to predict which individuals have an entrepreneurial profile, but we can work on developing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
2
3
0
Order By: Relevance
“…These findings are in line with numerous empirical studies that have supported the general positive effect of role models on entrepreneurial intentions (Chlosta et al, 2012;Laspita et al, 2012;Liñán & Fayolle, 2015;Urbano et al, 2011). Likewise, regarding NIEC, findings by Izquierdo and Buyens (2008), Bikse andRiemere (2013), andAlmeida (2020) confirmed that after a course or program intervention, students' self-assessments of their entrepreneurial self-efficacy were higher, and they have shown a greater capacity to offer new business concepts due to their better technical understanding in the sector. On the other hand, the p-value for Gender (p = 0.481 > 0.05) suggests that the Gender variable was not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These findings are in line with numerous empirical studies that have supported the general positive effect of role models on entrepreneurial intentions (Chlosta et al, 2012;Laspita et al, 2012;Liñán & Fayolle, 2015;Urbano et al, 2011). Likewise, regarding NIEC, findings by Izquierdo and Buyens (2008), Bikse andRiemere (2013), andAlmeida (2020) confirmed that after a course or program intervention, students' self-assessments of their entrepreneurial self-efficacy were higher, and they have shown a greater capacity to offer new business concepts due to their better technical understanding in the sector. On the other hand, the p-value for Gender (p = 0.481 > 0.05) suggests that the Gender variable was not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…The results also show that after the course, students' self-assessments of their entrepreneurial self-efficacy were higher. This finding corroborates with Almeida (2020), who observed that students in management exhibited a higher level of financial and economic literacy since they discussed this topic in the context of other courses, however computer science students shown a superior capacity to offer new business concepts due to their greater technical understanding in the sector. Likewise, Bikse and Riemere (2013) found that Latvia has a unified system of methodological materials that has been developed in four subject areas and can help students develop their entrepreneurial competences.…”
Section: Entrepreneurial Courses and Students' Entrepreneurial Compet...supporting
confidence: 89%
See 2 more Smart Citations
“…Several developments have since occurred that have opened up the conversation on the importance of ECs significant for the 4IR (Prifti et al, 2017;Abdullahi et al, 2020;Kruger and Steyn, 2021). The literature provides emerging evidence of a positive relationship between ECs and innovative outputs, where empirical evidence suggests that entrepreneurs must have the right ECs to undertake innovative projects (Arafeh, 2016;Lilleväli and Täks, 2017;Fernando, 2020;Tittel and Terzidis, 2020;Kruger and Steyn, 2021) and key ECs for I4.0 (Grzybowska and Łupicka, 2017;Prifti et al, 2017;Chaka, 2020;Lose and Kapondoro, 2020;Ramli, Rasul and Affandi, 2020;Plawgo and Ertman, 2021).…”
Section: Ecs and Innovation Capacity (Ic) Within 4irmentioning
confidence: 99%